Analisis Yohanes 14:16 Suatu Kajian Apologetika Doktrin Roh Kudus - Daud Balang; Eko Chandra Setiawan (STTII PURWOKERTO, 2022)
Criticism comes to the text of John 14:16. Criticism comes especially to the phrase